Diagnostic Performance of Clinicopathological Analytes in Otostrongylus circumlitis-Infected Rehabilitating Juvenile Northern Elephant Seals (Mirounga angustirostris) - Sheldon, Julie D.; Hernandez, Jorge A.; Johnson, Shawn P.; Field, Cara; Kaye, Sarrah; Stacy, Nicole I. (Frontiers in Veterinary Science, 2019)
The nematode lungworm, Otostrongylus circumlitis (OC), is a significant cause of northern elephant seal (NES; Mirounga angustirostris) mortality at The Marine Mammal Center (TMMC, Sausalito, CA). The current lack of specific antemortem diagnostic tests for pre-patent OC infection in NES makes diagnosis, proper treatment, and assessment of efficacy of medications challenging. Severe inflammation and disseminated intravascular coagulation (DIC) develop rapidly and are difficult to treat once clinical signs develop. Certain blood inflammatory and hemostasis biomarkers for early diagnosis have recently been investigated. The objective of this study was to investigate the diagnostic performance of complete blood count, serum chemistry, acute phase proteins, protein electrophoresis, and coagulation parameters for diagnosis of OC clinical infection in NES. Samples from NES with OC infection confirmed by gross pathology with blood collected antemortem during clinical disease (n = 9) and NES initially admitted for malnutrition and sampled shortly before release after successful rehabilitation (n = 20) were included in the study. Using Receiver operator characteristic (ROC) curve analysis, the diagnostic performances (area under the curve [AUC]) of albumin (0.994), albumin:globulin ratio (0.983), serum amyloid A (0.972), activated partial thromboplastin time (0.936), total bilirubin (0.975), and gamma-glutamyl transferase (0.939) were high (AUC > 0.9). These results confirm systemic inflammation and DIC, and support previously reported clinical and gross pathological findings in NES infected with OC. In addition to AUC values, this study produced cut-off points, sensitivity, specificity, confidence intervals, and predictive values for analytes with high diagnostic performance. This data will be useful in the diagnosis and clinical management of OC-infected NES and will aid in assessment of treatment efficacy.